2021
DOI: 10.1186/s12985-021-01546-8
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of post-COVID impairment: interim analysis of a prospective study from Czechia

Abstract: We stratified post-COVID patients into four newly established clinical groups based on the presence or absence of at least one subjective respiratory symptom and at least one objective sign of pulmonary involvement. Nearly half of outpatients and one third of hospitalized post-COVID patients had objective signs of pulmonary involvement without accompanying subjective respiratory symptoms three months after diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“… Radar chart illustrating the prevalence of the specific long COVID symptoms in the cohort studies with study number indicated on the circle circumference [ 15 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , ...…”
Section: Resultsmentioning
confidence: 99%
“… Radar chart illustrating the prevalence of the specific long COVID symptoms in the cohort studies with study number indicated on the circle circumference [ 15 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Published June 10, 2020 , Sabes-Figuera et al, 2010 , Winston, 2020 , Xu et al, 2017 , Stroup et al, 2000 , Page et al, 2021 , Better systematic review management. Published June 11, 2020 , Stang, 2010 , Shuwa et al, 2021 , Sonnweber et al, 2021 , Taboada et al, 2021 , Todt et al, 2021 , Wong et al, 2020 , Zhou et al, 2021 , Ghosn et al, 2021 , Say et al, 2021 , Pilotto et al, 2021 , Liyanage-Don et al, 2021 , Miyazato et al, 20202020 , González et al, 2021 , Fernández-de-las-Peñas et al, 2021 , Fernández-de-Las-Peñas et al, 2021 , Arnold et al, 2021 , Fortini et al, 2021 , García-Abellán et al, 2021 , Ong et al, 20212021 , PHOSP-COVID Collaborative Group et al, 2021 , Skala et al, 2021 , Sykes et al, 2021 , Santis et al, 2020 , van den Borst et al, 2020 , Venturelli et al, 2021 , IL6 - Clinical: Interleukin 6, Plasma. Accessed June 26, 2021 , Elkan et al, 2021 , Frontera et al, 2021 , Garrigues et al, 2020 , Havervall et al, 2021 , Rogers et al, 2020 , Hoffman and Vilensky, 2017 , Komaroff and Lipkin, 2021 , Higgins et al, 2021 , Douaud et al, 2021 , Lee et al, 2021 , Guedj et al, 2021 , Libby and Lüscher, 2020 , Oronsky et al, 2021 , Yong, 2021 , Sartori et al, 2012 , Rosenblat et al, 2014 , Sonneville et al, 2009 , Gałecki et al, 2018 , Heckenberg et al, 2018 , Xiong et al, 2020 , Taquet et al, 2021 , McIntyre et al, 2019 , …”
Section: Uncited Referencesmentioning
confidence: 99%
“…This might be due to higher sensitivity to minor reduction in respiratory function. Skala et al 25 found in their interim analysis of post-COVID-19 patients that the reporting of symptoms was more frequent in patients with higher levels of anxiety, especially in females. In their study, the pulmonary involvement was found mostly in hospitalized subjects where 77% of patients had significant pulmonary changes.…”
Section: Discussionmentioning
confidence: 99%